The Rhizosphere Microbiome of Mikania micrantha Provides Insight Into Adaptation and Invasion - Yin, Lijuan; Liu, Bo; Wang, Hengchao; Zhang, Yan; Wang, Sen; Jiang, Fan; Ren, Yuwei; Liu, Hangwei; Liu, Conghui; Wan, Fanghao; Wang, Haihong; Qian, Wanqiang; et al. (Frontiers in Microbiology, 2020)
Mikania micrantha is a noxious invasive plant causing enormous economic losses and ecological damage. Soil microbiome plays an important role in the invasion process of M. micrantha, while little is known about its rhizosphere microbiome composition and function. In this study, we identified the distinct rhizosphere microbial communities of M. micrantha, by comparing them with those of two coexisting native plants (Polygonum chinense and Paederia scandens) and the bulk soils, using metagenomics data from field sampling and pot experiment. As a result, the enrichment of phosphorus-solubilizing bacteria Pseudomonas and Enterobacter was consistent with the increased soil available phosphorus in M. micrantha rhizosphere. Furthermore, the pathogens of Fusarium oxysporum and Ralstonia solanacearum and pathogenic genes of type III secretion system (T3SS) were observed to be less abundant in M. micrantha rhizosphere, which might be attributed to the enrichment of biocontrol bacteria Catenulispora, Pseudomonas, and Candidatus Entotheonella and polyketide synthase (PKS) genes involved in synthesizing antibiotics and polyketides to inhibit pathogens. These findings collectively suggested that the enrichment of microbes involved in nutrient acquisition and pathogen suppression in the rhizosphere of M. micrantha largely enhances its adaptation and invasion to various environments.